2020
DOI: 10.1049/iet-its.2020.0184
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated control of steer‐by‐wire and brake‐by‐wire for autonomous emergency braking on split‐μ roads

Abstract: Autonomous emergency braking (AEB) is an active safety technology which aims to prevent collisions by operating harsh braking. When AEB is activated on split-μ roads, the yaw moment generated by the asymmetric braking forces will lead to losing control of the vehicle. In this study, a coordinated control scheme of steer-by-wire (SBW) and brake-by-wire (BBW) is developed to solve this problem. An anti-lock braking system is achieved by a sliding mode controller. Besides, two model predictive controllers based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…ABS adjusts brake torque by setting slip ratio and angular acceleration thresholds and achieves steering compensation and brake coordination through yaw rate thresholds. Its advantages lie in simplicity and independence from state observation, but it lacks robustness and overly relies on calibration, affecting driving comfort [19,20]. Some scholars have implemented ABS using slip mode control, taking actual and optimal slip ratios as inputs, designing a slip surface to output braking torque, and adjusting the actual slip ratio to the target.…”
Section: Introductionmentioning
confidence: 99%
“…ABS adjusts brake torque by setting slip ratio and angular acceleration thresholds and achieves steering compensation and brake coordination through yaw rate thresholds. Its advantages lie in simplicity and independence from state observation, but it lacks robustness and overly relies on calibration, affecting driving comfort [19,20]. Some scholars have implemented ABS using slip mode control, taking actual and optimal slip ratios as inputs, designing a slip surface to output braking torque, and adjusting the actual slip ratio to the target.…”
Section: Introductionmentioning
confidence: 99%
“…Park used vehicle dynamics and sensor fusion information to calculate the warning distance, and predicted the vehicle speed before the accident happens to determine the precise warning and braking time [10]. Chelbi pointed out that when the AEB braking is an emergency to prevent a collision, the yaw moment generated by the asymmetric braking force will result in losing control of the vehicle [11], and Xue found that the coordinated control of steer-by-wire (SBW) can solve the problem of vehicle loss of control caused by asymmetric yaw moment when AEB starts on mu-split road conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…WITH the improvement of people's living standards and the rapid development of automobile industry, people have higher requirements for the safety of road traffic, and autonomous emergency braking system (AEBS) has been widely used. It helps drivers to reduce the risk of collisions while driving on the road and raise the road safety level [1]. Generally, the architecture of AEBS includes three parts, namely sensing system, decision-making system, and execution system.…”
Section: Introductionmentioning
confidence: 99%